A HINGGA K TAHAP DASAR MENGARANSEMEN NYANYIAN UNTUK PADUAN SUARA - Wahyu Purnomo (Institut Seni Indonesia Surakarta, 2018)
Choir as a form of vocal music that uses human voice as its main media has a unique and interesting side of beauty, except for the beauty of melody, rhythm and harmony, the choir also delivers its message through the lyrics/verses that it sings has a sufficient number of enthusiasts many. The activities of singing or singing in groups, namely in the form of choirs in Indonesia in the last few years have shown remarkable progress both in terms of quantity and quality. Choir competitions held at national and international levels always invite high enthusiasm from choir activists or communities in Indonesia to participate. The choir competition held in the last few years, both national and international levels as mentioned above, uses a race classification system, which is based on music genres and certain times / periods of historical periods in western music. The use of the competition category system is accompanied by the rules of the organizer which usually gives freedom for each contestant to determine the song title and number of songs to be sung, so it does not require a particular song to be sung by each competitor.Along with the reality above and the increasingly competitive national level choir competition and the increasing enthusiasm of the Indonesian choir community to participate and excel at the international competition, the needs and availability of choir songs that have been arranged in good and interesting arrangements is believed will continue to increase. Writing with the title A to K of the single basic institution stage for sound alloy explains things that are fundamentally the main need for someone when they are interested in being able to master the way to make arrangements for the choir. Things that are described include: human voice coverage, voice range relationship with selection of basic scales or tones, understanding chords and their formation, chord types, chords in basic positions, I reversal and reversal II, Kadens, making harmonization, designing shapes composition, determining instrumentation, processing the elements of music, Based on the background of this, it is very necessary for an introduction to describe how to make arrangements for a choir song. The hope, with the increasing number of choir lovers who also have an interest in equipping themselves with developing their knowledge in terms of making arrangements for the choir, will in the future more and more management works be produced and certainly will enrich the literature of songs from the Spiritual category. secular, regional and pop songs for choir groups. This will also be beneficial for many choirs to maintain their existence in their musical activities.Keywords: sound, arrangement, single basic, A to K.